An Analysis of India's Trade Intensity with UAE - Goyal, Krishn Awatar; Vajid, Abdul (Journal of Commerce and Trade, 2018)
Today no nation in the world is fully self-reliant on its own resources. All the nations of the world are somehow interdependent on others, because every nation has its own natural resources, climate, geographical conditions and sources of energy. International interdependence is the main feature of today's global economy. Trading links between India and UAE have existed since ancient times. Indo-UAE trade has grown enormously in recent years. Many statistical trade indices are available to measure trade between two countries. One of them is the trade intensity index. The trade intensity index appears in two forms, the export intensity index and import intensity index. A few studies have done to explore intricacies of the trade relationship between the two countries. Under such scenario this paper investigates the major trends of bilateral trade and explores issues associated with trade intensity. An attempt is made here to examine the India's Trade Intensity with UAE for the period from 2006 to 2016. The paper also suggests measures to enhance trade intensity between India and UAE. Time series data have been used to measure Trade Intensity Index (TII). The findings of the study reveal that India's trade with UAE is more intense in comparison with its other trading partners. Classification-JEL : F13, F15, N15, N55